Productivity of "Non-Knowledge" (KULT_online, 2017)
In her monograph Die Produktion der Katastrophe: Das Tunguska-Ereignis und die Programme der Moderne, Solveig Nitzke interprets narratives of the “Tunguska”-event that shaped the corresponding discourse: as a riddle, as a catastrophe, as a myth, as a secret and as a historical incident. Between scientific and literary discourse on the one hand, and expert and lay research on the other, “Tunguska” threatens the orders and hierarchies of knowledge within modernity. Nitzke unfolds this nature-culture-hybrid and shows the productivity of “non-knowledge” for the study of culture.